A comparison of three transpiration models in a tomato crop grown under greenhouse conditions - Rivera-Zamarripa, Jaime (REVISTA TERRA LATINOAMERICANA, 2013)
Transpiration is a physiological process, which uses almost all the water absorbed by plants. In this investigation, the transpiration rate was estimated using three models Penman-Monteith, Stanghellini, and Boulard-Wang. Observed data were obtained from two experiments on tomato (Solanum lycopersicum L.) grown under greenhouse conditions and hydroponics. The first experiment was conducted during 13 days of June, 2008 at the University of Querétaro. The second experiment lasted 18 days during October and November, 2008, at the University of Chapingo. At both sites, transpiration rates in a tomato crop were measured using a weight lysimeter. Input variables of each model were recorded simultaneously and the leaf area index (LAI) of the crop was measured. In the summer at the Queretaro site, the model Boulard- Wang with a LAI = 1 had the best model performance according to both the model efficiency (EF = 0.72) and agreement index (AI = 0.92) statistics. On the other hand, at the Chapingo site, with lower air temperature, and a LAI = 2 the Sthangellini model had the best model performance obtaining an EF = 0.84 and AI = 0.96. The best model performance of Boulard-Wang model for the Queretaro data was mainly attributed to meteorological conditions (higher wind speed) outside the greenhouse, which reflected the high energy load (microadvection) inside the greenhouse. The sparse crop canopy (LAI = 1) was the main cause of the microadvection.